RILEY COUNTY HEALTH DEPARTMENT: HISPANIC OUTREACH PROJECT - Ramirez, Melitza Rios (My University, 2021)
It has been predicted that by 2025, the Latino/Hispanic population in the United States will increase from 31 million to 59 million (Carillo et al., 2011). The Hispanic population has encountered several healthcare barriers regarding healthcare services, including language barriers for Spanish-speaking Hispanic patients (Hu et al., 2013). Having language barriers often leads to a lack of healthcare information, due to not being able to understand instructions, as well as miscommunication between the patient and provider (Hu et al., 2013). Patients with limited English proficiency (LEP) often delay seeing a healthcare provider, experience a lack of confidence and confusion when seeking healthcare services, and are often unaware of access of interpretation and of other services provided (Harari et al., 2008). These barriers to seeking healthcare services likely contribute to greater health disparities among the Hispanic population. The purpose of this project was to determine the needs, barriers to access, and awareness of services provided by the Riley County Health Department among the Spanish speaking community members of Riley County, KS.
Keywords: Healthcare Barriers; Hispanics; Limited English Proficiency; Public Health; Spanish-speaking; Latino Health